The Effect of Triangulation-Based Metacognitive Learning Strategy on Students' Chemistry Literacy and Learning Achievement - Parlan Parlan; Zelen Surya Minata; Ida Bagus Suryadharma; Oktavia Sulistina; Siti Marfu'ah (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
This study aimed to investigate the effect of triangulation-based metacognitive learning strategy on students’ chemistry literacy and learning achievement. This study was conducted by using a pretest-posttest control group design. The participants of this research were two classes of 10th grade natural science students of Senior High School in Pasuruan, Indonesia. One class was taught using triangulation-based metacognitive learning strategies consisting of four steps (Preparing, Doing, Checking, and Assessing & Following-Up) abbreviated to MLS-PDCA, and another was taught using expository learning strategy (ELS). Data was collected by pretest and posttest. Based on the data analysis, it was known that the N-gain averages of students’ chemistry literacy were 54% in MLS-PDCA class as the middle category and 38% in the ELS class as middle category. N-gain averages of learning achievement were 56% in experiment class as middle category and 40% in ELS as middle category. Mann Whitney U and independent sample t-test showed that the improvement of students’ chemistry literacy and learning achievement in MLS-PDCA class was more significant than in the ELS class. It can be concluded that MLS-PDCA can enhance the students’ chemistry literacy and learning achievement in senior high school.